PENGEMBANGAN MODUL PERUBAHAN LINGKUNGAN MELALUI MODEL THINK PAIR SHARE TERINTEGRASIKAN NILAI-NILAI ISLAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ramadhan, Muhammad Aulia; Anas, Nirwana; Jayanti, Ummi Nur Afinni Dwi (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
A module is a complex learning medium, which contains basic learning activities. An environmental change module that is integrated with Islamic values is needed because Islamic values make students aware of the importance of keeping the environment clean. Based on aspects of validity, practicality, and effectiveness, this research aims to determine the feasibility of an environmental change module that is integrated with Islamic values. The ADDIE development research model was applied in this research. The validation sheet is used to determine the validity of the model. The validity of the module obtained a percentage of 100% on the material component, 88% on the media component, and 95.8% on the Islamic integrity component. Teacher and student questionnaire answers are used to find out how practical the module is. Practical teacher response was 97.2% and student response was 88%. The effectiveness of the module is obtained through pretest and posttest assessment questionnaires and attitudes. The pretest and posttest effectiveness results obtained an n-Gain value of 0.80 with a percentage of 80% and effectiveness through attitude assessment obtained an average value of 90. With these results, the module was declared suitable for use. Therefore, it is hoped that this module can be used in educational and scientific media in the future.